2014
DOI: 10.1080/17432979.2014.962093
|View full text |Cite
|
Sign up to set email alerts
|

Body psychotherapy for the treatment of severe mental disorders – an overview

Abstract: The evidence base for the effectiveness of body psychotherapy (BPT) in the treatment of severe mental disorders has improved much over the last decade; both methodologically robust randomised controlled trials and also qualitative studies demonstrated how BPT can contribute substantially to the treatment portfolio and help address chronic conditions and disorder-specific psychopathology. This paper summarises how BPT is utilised for the treating a range of severe mental disorders including mania and schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…'psycho-(bio)-dramatic role playing' (Röhricht, 2015); using props to maintain the therapeutic alliance (Manford, 2014); 'improvising together' (Odell-Miller, 2016) and; finding ways of becoming present to the patient through the arts form (Strehlow & Piegler, 2007). In terms of reflecting on relationships,) it is suggested that engaging in the arts enables relational patterns to be repeated (reenactments) (Strehlow & Piegler, 2007), establishing 'a new and reparatory relational model' (Cukier & Marmelszetjn, 1998), for example through enabling curiosity and interest in the patient (Springham, Findlay, et al, 2012), facilitating group curiosity and understanding interpersonal conflicts (Johns & Karterud, 2004).…”
Section: Processing Interpersonal Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…'psycho-(bio)-dramatic role playing' (Röhricht, 2015); using props to maintain the therapeutic alliance (Manford, 2014); 'improvising together' (Odell-Miller, 2016) and; finding ways of becoming present to the patient through the arts form (Strehlow & Piegler, 2007). In terms of reflecting on relationships,) it is suggested that engaging in the arts enables relational patterns to be repeated (reenactments) (Strehlow & Piegler, 2007), establishing 'a new and reparatory relational model' (Cukier & Marmelszetjn, 1998), for example through enabling curiosity and interest in the patient (Springham, Findlay, et al, 2012), facilitating group curiosity and understanding interpersonal conflicts (Johns & Karterud, 2004).…”
Section: Processing Interpersonal Experiencementioning
confidence: 99%
“…However this literature review does not provide more detail about the quality of the papers or the method of synthesis employed. Röhricht (2015) has also given an overview of body psychotherapy practice for severe mental health issues, however given the paucity of literature in this area about the treatment of PD only a few paragraphs refer to the treatment of this population. Studies with this client population are also notably absent from the meta-analysis completed by Koch et al (2014) in dance movement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence to support the use of non-verbal interventions in mental health care (Röhricht, 2009(Röhricht, , 2015. However, as far as ED are concerned, systematic reviews of RCTs on the effectiveness of physical therapy interventions concluded that, whilst promising, more evidence is required (Vancampfort et al, 2013(Vancampfort et al, , 2014.…”
mentioning
confidence: 99%
“…The evidence base for the effectiveness of body psychotherapy has improved much over the last decade (Röhricht, 2015). Practice-based clinical evidence and a few empirical studies point toward good efficacy of non-verbal interventions regarding emotional processing, movement behaviour and body experience.…”
Section: Introductionmentioning
confidence: 99%
“…Non-verbal intervention techniques are combined in a semi-structured protocol of six weekly one-hour sessions to target anger-related issues, for instance, critical inner voices toward the body, giving in to purging behaviours, guilt, shame or painful memories. In a previous article, we elaborated on the content of the aggression regulation module (Boerhout, van Busschbach, Wiersma, & Hoek, 2013).The evidence base for the effectiveness of body psychotherapy has improved much over the last decade (Röhricht, 2015). Practice-based clinical evidence and a few empirical studies point toward good efficacy of non-verbal interventions regarding emotional processing, movement behaviour and body experience.…”
mentioning
confidence: 99%